Interests, Economics and Emancipation. On Return of Critical Pedagogy to Socio-Economic Issues and Category of Intervention - Stańczyk, Piotr (INSTED: Interdisciplinary Studies in Education & Society, 2016)
The article deals with problem of class interests in contemporary critical theory in education. Eradication of social class from social sciences is side effect of postmodern inspirations. Although that kind of attitude is fundamentally critical it also is counterproductive because it brings indifference to question of socio-economic issues. The article aims at presenting return of American radical pedagogy to the notion of social class and class struggle (hooks 2000; McLaren 2000; 2005) inspired by philosophy of brazilian educator Paulo Freire. The second part of the text contains presentation of P. Freire?s (1975; 1992; 1998; 2000; 2001; Scocuglia 2005; Streck 2009). thought evolution from neutral to class-focused perspective in emancipatory education and then from emancipatory towards hegemony paradigm in the politics of education. In the end the concept of the intervention is considered as the way out from impasse of critical theory of education to the radical and revolutionary praxis engaged in social change for social justice.